Moderating role of counselling help-seeking attitudes on the relationship between perfectionism, love style and marital satisfaction among postgraduate students - Foo, Fatt Mee (2017)
Counseling services are provided by university counselors to promote students’ wellness. Despite increasing number of postgraduate students’ enrolment, the counseling services do not allocate much attention to them as compared to the undergraduate students. The postgraduate education could be a challenging journey, especially to the students who are married. Focusing on married postgraduate students, this research aims at achieving three objectives. The first objective of this research is to examine the relationship between perfectionism, love styles, and marital satisfaction. The second objective is to explore the latent mean difference in perfectionism, love styles, and marital satisfaction, between positive and negative attitudes toward counseling help-seeking groups. The third objective is to explore the moderating effect of counseling help-seeking attitudes on the relationships between perfectionism, love styles, and marital satisfaction.